Feminism in postmodern society: an Islamic perspective (2005)
In this research, an attempt is made to focus on the real nature of the challenges of postmodern feminism and its implications on not only Muslim women but also on the family and society at large. The research also examines the typology of this phenomenon known as Islamic feminism to reveal how some Muslim women are now confronting postmodern feminism in today's global village. The goal here is to provide a basis for exploring the main dimensions of postmodern feminism as central to practices in the Muslim world. It is hoped that this can stimulate Islamic organizations to address these dimensions in formulating their policies on women. The research will therefore reply to western feminist writers who unjustly believe that Islam treats women with utter scorn, injustice and humiliation. It will also demonstrate that Islam and what is now known as Islamic feminism are not incompatible if the eradication of women's oppression is the primary aim of feminism. It is not contradictory to Islamic tenets of equity, equality, and justice for all races, groups and sexes. The study concludes that labeling any political and intellectual activisms in support of Muslim women's public roles in society "Islamic feminism" will show the difference between Islam, a religion that preaches moderacy in any human endeavor, and the extremism of secular postmodern feminism.